Free vibration analysis of porous nanoplates using NURBS formulations - Phuc, Phung Van; Khanh, Chau Nguyen; Khai, Chau Nguyen; Hung, Nguyen Xuan (Vietnam Journal of Science and Technology, 2020)
This paper presents free vibration analysis of functionally graded (FG) porous nanoplates based on isogeometric approach. Material properties of the nanoplates are given by using a modified power-law function. The Eringen’s nonlocal elasticity is used to capture the size effects. Based on a combination of the Hamilton’s principle and the higher order shear deformation theory, the governing equations of the porous nanoplates are derived. The obtained results demonstrate the significance of nonlocal parameter, porosity volume fraction, porosity distributions and volume fraction exponent on free vibration analysis of the nanoplates with porosities.